(untitled) (Swiss Medical Weekly, 2019)
BACKGROUND Acute pain is the most common complaint of patients presenting to emergency departments (EDs). Effective pain management is a core ED mission, but numerous studies have pointed to insufficient pain treatment or oligoanalgesia. According to a 1997 national survey in Swiss EDs, a validated pain scale was used in only 14%, an analgesia protocol in <5%, and 1.1% had a nurse-initiated pain protocol. Since then, numerous societal and health care factors have led to improved ED pain care. The aim of this study was to assess the state of ED pain management in Switzerland. METHODS Hospital-based Swiss EDs open 24 hours a day and 7 days a week in 2013 were surveyed using a questionnaire. Data from 2013 were collected. Questions queried the pain management process by nurses and physicians in each ED. RESULTS The response rate was 115 of 137 eligible EDs (84%). Pain intensity was assessed with a validated instrument in 71% of waiting rooms and in 99% of treatment areas. A nurse-initiated analgesia protocol was available in 56% of waiting rooms and in 70% of treatment areas. Physician pain protocols were available in 75%, and analgesia-sedation protocols in 51%. CONCLUSION The pain management processes in Swiss EDs have improved over the last 17 years, and are now equivalent to other western countries. Our study did not, however, assess if these improvements resulted in better analgesia at the bedside, an important topic that will require further study.